Theta burst stimulation over left cerebellum does not modulate auditory feedback control of vocal production - Liu, Dongxu; Chen, Mingyun; Lin, Qing; Li, Tingni; Chen, Xi; Dai, Guangyan; Wu, Xiuqin; Li, Jingting; Liu, Hanjun; Liu, Peng (Frontiers in Neuroscience, 2022)
Accumulating evidence has shown significant contributions of the right cerebellum to auditory-motor integration for vocal production. Whether the left cerebellum is likewise involved in vocal motor control, however, remains unclear. By applying neuronavigated continuous and intermittent theta burst stimulation (cTBS/iTBS) over the left cerebellar lobule VII (Crus I), the present event-related potential (ERP) study investigated whether the left cerebellum exerts causal effects in modulating auditory feedback control of vocal pitch production. After receiving cTBS, iTBS, or sham stimulation over the left cerebellum, a group of fifteen young adults produced sustained vowels while hearing their voice unexpectedly shifted in pitch upwards or downwards by 200 cents. The effects of cerebellar stimulation were assessed by measuring the vocal and ERP (N1/P2) responses to pitch perturbations across the conditions. When compared to sham stimulation, cTBS or iTBS over the left cerebellar lobule VII (Crus I) led to no systematic changes in vocal compensations for pitch perturbations in auditory feedback. Also, the cortical N1/P2 responses did not vary significantly across the three stimulation sessions. These findings present the first neurobehavioral evidence suggesting that the left cerebellum is not causally associated with auditory feedback control of vocal production. Together with previously reported causal effects of the right cerebellum in modulating vocal pitch regulation, the present study lends support to the hypothesis that there is a functional lateralization of the cerebellum in vocal motor control though auditory feedback.